Implementasi terkait Keberhasilan Pembangunan Apartemen Graha Aparna: dalam Konteks Publik Servis kepada Penghuni Apartemen Graha Aparna - Rawung, Yemima Marchely; Muljanto, Muhammad Agus (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Land limitations, especially in big cities like DKI Jakarta and Surabaya, have caused land prices to skyrocket in all areas. This has made apartments and condominiums a popular choice for consumers. Additionally, the strategic location of apartments makes them a more affordable option compared to very expensive condominiums in big cities. However, the increase in apartment sales has also led to an increase in fraudulent practices by real estate developers, causing consumers to suffer significant losses as a result of this phenomenon. The specific issue is the commercialization of housing construction projects that have not been implemented but have been publicly marketed. This research is conducted and addressed to the development of Graha Aparna Apartments with the aim of examining the community's perspective on the environmental and social conditions in the development area of Graha Aparna Apartments. The research method used is descriptive qualitative research and literature study of journals or books referenced in the process of examining these issues.